2022
DOI: 10.1038/s42003-022-04138-6
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike opening dynamics and energetics reveal the individual roles of glycans and their collective impact

Abstract: The trimeric spike (S) glycoprotein, which protrudes from the SARS-CoV-2 viral envelope, binds to human ACE2, initiated by at least one protomer’s receptor binding domain (RBD) switching from a "down” (closed) to an "up” (open) state. Here, we used large-scale molecular dynamics simulations and two-dimensional replica exchange umbrella sampling calculations with more than a thousand windows and an aggregate total of 160 μs of simulation to investigate this transition with and without glycans. We find that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(97 citation statements)
references
References 84 publications
6
91
0
Order By: Relevance
“…Structural analysis revealed that the RBD could possess up and down configurations, in which an up-conformation favors the interaction with ACE2 or ACE2-blocking neutralization antibodies [ 32 , 41 , 48 , 49 , 50 , 51 ], while the RBD in down-conformation masks ACE2-interacting interfaces and hides potential antigenic epitopes [ 52 ] ( Figure 2 B). The configurations of the RBD can be additionally regulated by glycans, fatty acids, and physical temperature [ 52 , 53 , 54 ], or individual mutations within the S1 subunits, such as amino acid substitution at the D614G [ 55 , 56 ] or altered hydrophobicity at S375F [ 57 ]. Nevertheless, the S1 subunit senses the entry signal derived from target cell receptor binding and translates it into the activating signal for the S2 subunit.…”
Section: The Sars-cov-2 Spikementioning
confidence: 99%
“…Structural analysis revealed that the RBD could possess up and down configurations, in which an up-conformation favors the interaction with ACE2 or ACE2-blocking neutralization antibodies [ 32 , 41 , 48 , 49 , 50 , 51 ], while the RBD in down-conformation masks ACE2-interacting interfaces and hides potential antigenic epitopes [ 52 ] ( Figure 2 B). The configurations of the RBD can be additionally regulated by glycans, fatty acids, and physical temperature [ 52 , 53 , 54 ], or individual mutations within the S1 subunits, such as amino acid substitution at the D614G [ 55 , 56 ] or altered hydrophobicity at S375F [ 57 ]. Nevertheless, the S1 subunit senses the entry signal derived from target cell receptor binding and translates it into the activating signal for the S2 subunit.…”
Section: The Sars-cov-2 Spikementioning
confidence: 99%
“… 9 , 38 The glycans represent ∼25% of the mass 9 and cover ∼40% of the surface area 12 of the SARS-CoV-2 S protein. Collectively, these glycans create a protective shield on the spike protein to avoid detection by the immune system 10 , 11 , 15 ( Figure 2 A). However, an average representation of the covered surface area may not be conclusive evidence of glycans’ shielding effect since some can be removed from their binding site by the antibody.…”
Section: Impact Of S-protein Glycansmentioning
confidence: 99%
“…(B) S-protein glycans at N165, N234, and N343 play intricate roles in stabilizing the down and the up state. The top and bottom panels are reproduced with permission from ref ( 10 ) (Copyright 2020 American Chemical Society) and ref ( 15 ) (Copyright 2022 Gumbart and co-workers), respectively.…”
Section: Impact Of S-protein Glycansmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations provided important atomistic and mechanistic advances into understanding the dynamics and function of the SARS-CoV-2 S proteins. All-atom molecular dynamics (MD) simulations of the full-length SARS-CoV-2 S glycoprotein embedded in the viral membrane, with a complete glycosylation profile provided detailed characterization of the conformational landscapes of the S proteins in the physiological environment [56][57][58][59][60][61]. Using distributed cloudbased computing, large scale MD simulations of the viral proteome observed dramatic opening of the S protein complex, predicting the existence of several cryptic epitopes in the S protein [62].…”
mentioning
confidence: 99%